Theme-based Instruction and Factors Affecting Non-English Major Students’ Motivation and Engagement in EFL Teaching and Learning Activities - Eryansyah Eryansyah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Students’ motivation and engagement are two crucial variables in EFL teaching. One strategy to improve them is via altering teaching approaches. Theme-based instruction was deemed effective in boosting EFL students’ motivation and engagement. The reason for conducting this study was to assess how theme-based instruction affected the motivation and engagement of non-English major students in EFL teaching and learning activities. A mixed-method research approach was employed to uncover elements that boosted students’ motivation and engagement in learning English utilizing theme-based instruction. The respondents employed in this study were students of a history education study program from a state-owned university in South Sumatra, Indonesia. Interviews and questionnaires were utilized to collect data for this study. While data from interviews were evaluated thematically, data from questionnaires were analyzed using SPSS. The results of the questionnaire demonstrated higher mean scores for attitude toward the approach, affect, motivation, self-confidence, and sense of improvement before and after the students' EFL teaching and learning activities were intervened with a theme-based instructional approach. These statistics demonstrated positive impact of theme-based educational approach. Findings from interviews revealed three elements affecting students’ motivation and engagement in EFL teaching with the approach. These included teacher factors, peer and teacher impact, and sense of improvement in English learning. In summary, theme-based instruction increased non-majoring-in-English students' performance in EFL teaching and learning activities.